P, Pemanfaatan PEMANFAATAN COCOPEAT SEBAGAI MEDIA TANAM DAN EKSTRAK BAWANG MERAH TERHADAP PERTUMBUHAN BIBIT TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq) DI PRE NURSERY - Ginting, Ade Ricky Atmaja; Razali Tanjung; Sijabat, Octanina Sari; Irwan Agusnu Putra (Agroprimatech, 2024)
The purpose of the study was to determine the effect of giving cocopeat as a planting medium and the results of onion extract on the growth of oil palm plants in pre nursery. This research was conducted at the People's Garden, Kel. Binjai Estate, Kec. South Binjai. Binjai City, North Sumatra, from December 2023 to March 2024. The research used a Factorial Randomized Group Design (RAK) with 2 treatment factors, the first factor Cocopeat consists of 3 levels of treatment, C0 = No cocopeat, only a mixture of topsoil with cow manure, C1 = 25% cocopeat and 75% topsoil mixture with cow manure, C2 = 50% cocopeat and 50% topsoil mixture with cow manure. The second factor, shallot extract with three treatment levels, namely E0 = 0 ml, E1 = 10 ml, and E2 = 20 ml. The parameters observed consisted of stem diameter (mm), plant height (cm), leaf area (cm2) and number of leaves (strands). The results showed that cocopeat treatment had a very significant effect on the growth of plant height, number of leaves and stem diameter. C2 (50% cocopeat and 50% topsoil mixture with cow manure) is the best treatment. The shallot extract treatment showed a significant effect on the growth of plant height, leaf area, and number of leaves, E2 (20 ml of shallot extract) was the best treatment.